Growth of cut roses under application of products with physiological effects - Almeida, Higor Mcarter Senra; Sabino, João Henrique Ferreira; Silva, Maria de Lourdes Neres da; Freitas, Victoria Jéssica Galvão de; Ramos, Anamaria Ribeiro Pereira; Beckmann-Cavalcante, Márkilla Zunete (Comunicata Scientiae, 2018)
The cultivation of cut roses can be compromised when cultivated in regions where climatic conditions are limiting for their adequate growth and development, so it is necessary to use appropriate technologies and inputs for their production. The application of products that promote physiological changes in the plant, such as fungicides or plant regulators might be viable technologies for rose production. The objective of this study was to evaluate the growth of cv. Carola under application of products with physiological effects cultivated in the Valley of the submedium São Francisco. The experimental design was a randomized complete block design in a 6 x 6 factorial design, with 6 products with physiological action (control - application of water, boscalid, pyraclostrobin, boscalid + pyraclostrobin, fluxapyroxad + pyraclostrobin and plant growth regulator) and 6 periods of analysis (40, 68, 124, 180, 236 and 292 days after transplantation, DAT) with four replicas of 12 plants each. Throughout the dates were evaluated the number of leaves, leaf area, total leaf chlorophyll, dry mass of leaves, stems, flowering branches, total dry mass, production of stems per plant and the biomass partition. There were significant differences for all variables studied except for the production of stems per plant. Regarding the biomass partition, a variation of values among applied products was observed over time, however, fluxapyroxad + pyraclostrobin and the growth regulator presented a balance among the dry mass of leaves, stem and flowering branches. The application of products belonging to the group of strobilurins as well as growth regulators is promising for the cultivation of cut roses in the semiarid.